Identification and Characterization of 5′ Untranslated Regions (5′UTRs) in Zymomonas mobilis as Regulatory Biological Parts - Cho, Seung Hee; Haning, Katie; Shen, Wei; Blome, Cameron; Li, Runxia; Yang, Shihui; Contreras, Lydia M. (Frontiers in Microbiology, 2017)
Regulatory RNA regions within a transcript, particularly in the 5’ untranslated region (5’UTR), have been shown in a variety of organisms to control the expression levels of these mRNAs in response to various metabolites or environmental conditions. Considering the unique tolerance of Zymomonas mobilis to ethanol and the growing interest in engineering microbial strains with enhanced tolerance to industrial inhibitors, we searched natural cis-regulatory regions in this microorganism using transcriptomic data and bioinformatics analysis. Potential regulatory 5’UTRs were identified and filtered based on length, gene function, relative gene counts, and conservation in other organisms. An in vivo fluorescence-based screening system was developed to confirm the responsiveness of 36 5’UTR candidates to ethanol, acetate, and xylose stresses. UTR_ZMO0347 (5’UTR of gene ZMO0347 encoding the RNA binding protein Hfq) was found to down-regulate downstream gene expression under ethanol stress. Genomic deletion of UTR_ZMO0347 led to a general decrease of hfq expression at the transcript level and increased sensitivity for observed changes in Hfq expression at the protein level. The role of UTR_ZMO0347 and other 5’UTRs gives us insight into the regulatory network of Z. mobilis in response to stress and unlocks new strategies for engineering robust industrial strains as well as for harvesting novel responsive regulatory biological parts for controllable gene expression platforms in this organism.